PAI-1 inhibits development of chronic otitis media and tympanosclerosis in a mouse model of otitis media. (December 2014) - Shin, Seul Gi; Koh, Seo Hyun; Woo, Chang-Hoon; Lim, Jae Hyang
Abstract Conclusion: Bullae of type 1 plasminogen activator inhibitor (PAI-1) knockout (KO) mice showed low levels of inflammation against nontypable Haemophilus influenzae (NTHi) at the early stage of otitis media (OM). However, PAI-1 KO mice fail to terminate inflammation, which may significantly contribute to the development of tympanosclerosis in PAI-1 KO mice. Objective: To investigate the role of PAI-1 in the pathogenesis of OM and subsequent tympanosclerosis. Methods: OM was induced with NTHi in PAI-1 KO and background control C57BL/6 mice. mRNA expression of PAI-1, tissue-type plasminogen activator (tPA), and urokinase-type plasminogen activator (uPA) was measured in the bullae of C57BL/6 mice. mRNA expression of interleukin (IL)-1β, tumor necrosis factor (TNF) α, macrophage inflammatory protein (MIP-2), tPA, and uPA in PAI-1 KO and C57BL/6 mice was compared. Histological changes produced by OM were compared at 1, 3, and 7 days after NTHi inoculation. Results: NTHi up-regulated the expression of PAI-1 and tPA in the bullae of C57BL/6 mice, but not uPA. mRNA expression of IL-1β, TNFα, and MIP-2 was low in PAI-1 KO mice at early time points, but significantly higher at the later stage of OM. Similarly to the gene expression results, histological changes associated with OM were less at days 1 and 3 in PAI-1 KO mice. However, unlike the gradual resolution of OM pathologies in C57BL/6 mice, PAI-1 KO mice showed significant pathological changes of tympanosclerosis.